A Strategy for Implementing The Quizizz Game-Based Learning Tool to Motivate Fifth-Grade Students at State Elementary School 1 Jelapat - Mitra Dewi; Abdul Rahman Azahari; Nyoto Nyoto (Jurnal Indonesia Sosial Sains, 2026)
This study aims to describe the implementation strategy of the Quizizz game-based learning media in providing learning motivation for grade V students of State Elementary School1 Jelapat. The research uses a qualitative approach with descriptive methods and case study design. The research subjects consisted of homeroom teachers and class V students. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman interactive model which included data reduction, data presentation, and conclusion drawn. The validity of the data was obtained through source triangulation, technical triangulation, and member check. The results of the study show that the Quizizz implementation strategy is carried out in a planned manner through the planning, implementation, and evaluation stages of learning. Teachers place Quizizz as a medium for reinforcement and evaluation after the delivery of the core material, as well as utilize the features of points, ratings, deadlines, and direct feedback to create an interactive and fun learning atmosphere. The use of Quizizz is able to increase students' motivation to learn, both intrinsically and extrinsically, which is shown through increased enthusiasm, involvement, and activeness of students during learning. The obstacles faced are limited devices, unstable internet networks, and differences in students' digital abilities, but can be overcome through teachers' adaptive strategies. The research concludes that the Quizizz game-based learning media can be an effective learning strategy to increase learning motivation in elementary school if implemented appropriately and contextually.